Confounding effects of socioeconomic status on the association between long-term PM2.5 exposure and mortality in Korea - Lim, Hyungryul; Choi, Jonghyuk; Bae, Sanghyuk; Choi, Kyung Hwa; Han, Xue; Ha, Mina; Kim, Jong Hun; Kim, Soontae; Kwon, Ho Jang (International Journal of Epidemiology, 2025)
Background: This study assesses the national distribution of ambient fine particulate matter (PM2.5) exposure across socioeconomic status (SES) and its confounding on long-term PM2.5 mortality in Korea, aiming to minimize SES influence. Methods: A nationwide cohort of 5% of Koreans, aged 30 or older, from 2007 to 2019, from the National Health Information Database, was analysed. PM2.5 exposure levels were estimated at the city level using the Community Multiscale Air Quality system. Mortality data were obtained from Statistics Korea. The study examined annual PM2.5 exposure by SES indicators and its confounding on mortality risks associated with PM2.5, using time-varying Cox proportional hazards models. Results: The study followed 1 453 036 individuals from 2007 to 2019, totalling 17 760 227 person-years (PYs). The non-accidental (A00-R99), cardiovascular (I00-I99) and respiratory (J00-J99) mortality rates per 1000 PY were 7.6, 1.9 and 0.8, respectively. We observed a trend of decreasing PM2.5 exposure levels but increased mortality among medical aid beneficiaries, those with lower household incomes and those residing in neighbourhoods with a higher area deprivation index. When adjusting for these SES covariates, the long-term mortality effects of PM2.5 shifted in the direction of increased risk [hazard ratio (HR) for cardiovascular mortality in the unadjusted model = 0.968 (95% CI: 0.909–0.959); HR in the fully adjusted model = 1.053 (95% CI: 1.004–1.105)]. Conclusion: In regions where SES and PM2.5 concentrations are positively correlated, as in Korea, it is crucial to rigorously control for SES confounding to avoid underestimating the mortality effects associated with PM2.5
Keywords: Adult; Aged; Aged, 80 and over; Air Pollutants; Air Pollution; Cardiovascular Diseases; Environmental Exposure; Female; Humans; Male; Middle Aged; Mortality; Particulate Matter; Proportional Hazards Models; Republic of Korea; Respiratory Tract Diseases; Social Class; cohort; confounding; Fine particulate matter; mortality; socioeconomic status